Sistem Pengajuan Judul Tugas Akhir Di Universitas Ekasakti Arsitektur Model View Controller - Harry Setya Hadi; Wahyuni Yahyan (Ikatan Ahli Informatika Indonesia, 2020)
The final project is a requirement for a student to get a bachelor's degree at any State Higher Education (PTN) or Private Higher Education (PTS) in Indonesia. In the preparation of the final project, the initial stage that must be done is submitting a title. Submission of the title of the final project at Ekasakti University, especially in the D3 Informatics and Computer Management study program, still uses a manual process. The technology that supports this title submission system uses the web as the basis and the architecture uses the Model View Controller, with web technology accessible to all people on campus, especially students, because the system is accessed online. The implementation of the Model View Controller which cannot process data (models) with a user interface design (view) which then controls the data that depends on the architecture (Controller) which facilitates system development by programmers. The results to be achieved in making this application system is the creation of a final assignment submission system.